Attention‐deficit hyperactivity disorder is associated with relatively short stature among adolescents. (24th January 2023) - Namimi‐Halevi, Chen; Dor, Chen; Dichtiar, Rita; Bromberg, Michal; Sinai, Tali
Abstract: Aim: To estimate the association between attention‐deficit hyperactivity disorder (ADHD) and relatively short stature (RSS) among adolescents. Methods: Participants in the Israeli Youth Health and Nutrition Survey (2015–2016), a cross‐sectional school‐based study, completed self‐administered questionnaires and underwent anthropometric measurements. Height z‐score < −0.7 (<25th percentile) was defined as RSS. Multivariable logistic regression analyses assessed the relation between ADHD and RSS, controlling for age, sex, body mass index (BMI) and socioeconomic status (Basic Model), and also for lifestyle factors such as physical activity, sleep duration, dietary patterns and intakes. Results: Of 4173 participants (11–18 years, 50.2% males), 654 self‐reported ever being diagnosed with ADHD; 3519 participants were controls. Overweight (BMI z‐score ≥1) and pubertal status were not different among groups. According to the Basic Model, ADHD was significantly associated with RSS (OR 1.25, 95% CI 1.03–1.50), and even after adjustments for lifestyle factors and dietary intake (OR 1.28, 95% CI 1.03–1.58). Stimulant‐treated ADHD adolescents had similar height z‐scores and lifestyles as those not treated with stimulants. Conclusion: Attention‐deficit hyperactivity disorder was associated with RSS. Height deficit may be intrinsic to ADHD or its pharmacotherapy, rather than a consequence of lifestyle alone. Further studies are needed to determine the causal relationship between ADHD and short stature.